Use of contraceptives and risk of inflammatory bowel disease: a nested case–control study. Issue 3 (18th October 2021) - Pasvol, Thomas Joshua; Bloom, Stuart; Segal, Anthony Walter; Rait, Greta; Horsfall, Laura
Summary: Background: How contraceptive formulation, dose, duration of therapy and mode of delivery affects the risk of inflammatory bowel disease (IBD) is poorly described. Aim: To examine associations between types of hormonal contraception and development of IBD. Methods: This was a nested case–control study using IQVIA Medical Research Data. Women aged 15‐49 years with a new diagnosis of IBD were matched with up to six controls by age, practice and year. Odds ratios (OR) and 95% confidence intervals (95% CI) for incident IBD and use of contraception were calculated. Results: 4932 incident cases of IBD were matched to 29 340 controls. Use of combined oral contraceptive pills (COCPs) was associated with the development of Crohn's disease and ulcerative colitis (OR 1.60 [1.41‐1.82] and 1.30 [1.15‐1.45], respectively). Each additional month of COCP exposure per year of follow‐up increased risk of Crohn's disease by 6.4% (5.1%‐7.7%) and ulcerative colitis by 3.3% (2.1%‐4.4%). Progestogen‐only pills had no effect on Crohn's disease risk (OR 1.09 [0.84‐1.40]) but there was a modest association with ulcerative colitis (OR 1.35 [1.12‐1.64]). Parenteral contraception was not associated with the development of Crohn's disease or ulcerative colitis (OR 1.15 [0.99‐1.47] and 1.17 [0.98‐1.39], respectively). Conclusions: We observed an increase in the risk of IBD with increasing duration of exposure to COCPs. Progestogen‐only pills were not associated with Crohn's disease but there was a modest association with ulcerative colitis. There was no association between parenteral progestogen‐only contraception and IBD. These findings are broadly consistent with a hypothesis that the oestrogen component of contraception may drive IBD pathogenesis. Abstract : Nested case‐control study including 4932 IBD cases matched to 29 340 controls. Use of oestrogen‐containing contraception was associated with development of both CD and UC. Progestogen‐only pills were not associated with CD but there was a modest association with UC. Parenteral progestogen‐only methods were not associated with IBD. The oestrogen component of contraception may drive IBD pathogenesis.